2021
DOI: 10.1016/j.bioactmat.2021.03.019
|View full text |Cite
|
Sign up to set email alerts
|

A structure-supporting, self-healing, and high permeating hydrogel bioink for establishment of diverse homogeneous tissue-like constructs

Abstract: The ready-to-use, structure-supporting hydrogel bioink can shorten the time for ink preparation, ensure cell dispersion, and maintain the preset shape/microstructure without additional assistance during printing. Meanwhile, ink with high permeability might facilitate uniform cell growth in biological constructs, which is beneficial to homogeneous tissue repair. Unfortunately, current bioinks are hard to meet these requirements simultaneously in a simple way. Here, based on the fast dynamic crosslinking of alde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 89 publications
2
43
0
Order By: Relevance
“…24,54 Chemical crosslinking can also be toxic to cells, but the SG approach has been used extensively and show low toxicity. [55][56][57] In this work, we created a library of gels and looked at cell survival. The gels that showed maximum longterm survival, adhesion, migration, and capillary-like network formation (4 : 1 and 8 : 1-75% PLL gels) have a low concentration of PAA in the hydrogel and the lowest number of free amines in the system (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…24,54 Chemical crosslinking can also be toxic to cells, but the SG approach has been used extensively and show low toxicity. [55][56][57] In this work, we created a library of gels and looked at cell survival. The gels that showed maximum longterm survival, adhesion, migration, and capillary-like network formation (4 : 1 and 8 : 1-75% PLL gels) have a low concentration of PAA in the hydrogel and the lowest number of free amines in the system (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro and in vivo experiments showed the favorable cell viability, attachment and proliferation, and obvious chondrogenic expression to verify the cartilage regeneration ( He et al, 2020 ). Chen et al synthesized a structure-supporting, self-healing, and high permeating hydrogel bio-ink, which was composed of aldehyde HA (AHA)/N-carboxymethyl chitosan (CMC) and gelatin (Gel)/4-arm poly (ethylene glycol) succinimidyl glutarate (PEG-SG) ( Chen et al, 2021 ). The obtained hydrogel bio-inks possessed good printability, self-healing capacity, and high permeability, thus achieving long-term cell viability, attachment, and growth for biological application ( Figure 6 ).…”
Section: Polymer-based Bioprinting Hydrogels For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…(E) Proliferation pattern of cells in low permeating constructs. Reproduced from Chen et al, (2021 ) with permission from Copyright 2021 Elsevier.…”
Section: Polymer-based Bioprinting Hydrogels For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…These materials are also widely used in drug delivery applications for the controlled release of hydrophobic drugs. Chen et al developed a structure for supporting hydrogel bioink, containing aldehyde hyaluronic acid, N-carboxymethyl chitosan, gelatin, and PEG succinimidyl glurate [101]. They demonstrated that this bioink enabled the printing of constructs with viscoelastic properties and self-healing behaviour with the potential for use in cartilage tissue engineering applications.…”
Section: Synthetic Biomaterial-based Bioinksmentioning
confidence: 99%